The role of epithelial cells in atopy pathogenesis - A. N. Kazimirsky; J. M. Salmasi; G. V. Poryadin; O. A. Svitich; B. G. Bragvadze; A. A. Alekseeva; L. V. Gankovskaya (Бюллетень сибирской медицины, 2019)
Aim. The study of the mechanisms of atopic disease formation and a model of immunopathogenesis of the atopic diseases.Methods. Determination of surface lymphocytes receptors in peripheral blood of atopic bronchial asthma and atopic dermatitis patients with the help of monoclonal antibodies using the indirect immunofluorescence method. Expression of genes encoding TLR2, TLR4 and TLR9 receptors of airborne epithelial cells by real-time polymerase chain reaction, as well as determination of cytokine TSLP, IL-33, IL-4 and TGFβ (eBioscience) in airway flushes in atopic asthma patients and healthy people.Results. During the exacerbation of atopic diseases in peripheral blood lymphocytes, an intensive activation process develops with impaired lymphocytes activating apoptosis aimed at the formation of plasma cells capable of developing intensive IgE synthesis. To search for signals that could explain the mechanism of rearrangement of the B-cell part of the immune system during atopy, the epithelium cells of the airways were examined in a group of patients with atopic asthma and found an increase in gene expression coding for TLR2, TLR4, TLR9 in 6, 3 and 2.5 times respectively. Along with increased expression of TLRs genes in patients with bronchial asthma, an increased content of TSLP and IL-33 cytokines secreted by epithelial cells of the airways was detected. These cytokines have an immunoregulatory action - their nearby antigen presenting functions format the Th2 type of immune response, promote the production of cytokines (IL-4, IL-9, IL-13) and cause the development of an allergic type of inflammation.Conclusion. We suppose that the main link in pathogenesis is a disruption of the interaction of TLRs with the corresponding ligands caused by spontaneous dimerization of TLRs under the malonic dialdehyde influence. The intake of slowly metabolized dimers of TLRs into epithelial cells is a signal for genome activation, which leads to the synthesis of allergic cytokines IL-33 and TSLP. Thus, the main immunopathogenesis pathway of atopic diseases is the pathological functional interaction between epithelial cells and peripheral blood B-lymphocytes.